2021
DOI: 10.1111/emre.12457
|View full text |Cite
|
Sign up to set email alerts
|

Change the way of working. Ways into self‐organization with the use of Holacracy: An empirical investigation

Abstract: Holacracy, a self‐managing design for organizations, uses the radical decentralization of authority and a lack of a manager‐subordinate relationship. It differs significantly from traditional organizational forms, and in particular, the transformation of the organization from a traditional to a holacratic system brings with it various challenges, especially for employees and teams that need to be resolved, so organizations can realize their potential. This study uses an explorative case study design with 43 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
(61 reference statements)
2
17
0
2
Order By: Relevance
“…The absence of hierarchy and improved feedback contribute to a respectful work climate and appreciation among the team (Kottwitz et al, 2019). Results of a recently published study support these findings, which identified that holacracy creates an opportunity for appreciation since all tasks and functions become visible and cannot be overlooked anymore (Schell and Bischof, 2021). Moreover, the fact that in meetings roles and tasks are constantly reviewed leads to high transparency and awareness regarding the importance of each task (Schell and Bischof, 2021).…”
Section: Appreciation At Work In Holacracymentioning
confidence: 79%
See 1 more Smart Citation
“…The absence of hierarchy and improved feedback contribute to a respectful work climate and appreciation among the team (Kottwitz et al, 2019). Results of a recently published study support these findings, which identified that holacracy creates an opportunity for appreciation since all tasks and functions become visible and cannot be overlooked anymore (Schell and Bischof, 2021). Moreover, the fact that in meetings roles and tasks are constantly reviewed leads to high transparency and awareness regarding the importance of each task (Schell and Bischof, 2021).…”
Section: Appreciation At Work In Holacracymentioning
confidence: 79%
“…Results of a recently published study support these findings, which identified that holacracy creates an opportunity for appreciation since all tasks and functions become visible and cannot be overlooked anymore (Schell and Bischof, 2021). Moreover, the fact that in meetings roles and tasks are constantly reviewed leads to high transparency and awareness regarding the importance of each task (Schell and Bischof, 2021). Based on these findings, the following hypothesis was formulated: Hypothesis 2.…”
Section: Appreciation At Work In Holacracymentioning
confidence: 80%
“…Authority is exercised through these roles and positions, by persons in authority or through the creation of procedures to be followed—decisions are taken by some individuals, and procedures are decided, that are to be accepted and carried out by other individuals. Existing studies make it clear that in self‐managing or holacratic organizations, authority takes radically decentralized forms but is inescapably present (Schell & Bischof, 2021).…”
Section: The Deontic Source Of the Distinct Efficiency Of Firmsmentioning
confidence: 99%
“…De meest vergaande variant van heterarchische organi saties is de zelfsturende organisatie, ook wel organische organisatie genoemd (Laloux 2015). Holacracy past bij deze uiterste vorm, omdat het een volledig geformaliseer de manier van zelfsturing is en geschikt is voor radicale decentralisatie op grote schaal (Lee and Edmondson 2017;Schell and Bischof 2021). Het biedt een nieuwe organi satiestructuur die sterk afwijkt van traditionele hiërarchi sche organisaties.…”
Section: Holacracyunclassified
“…Alle rollen zijn verantwoordelijk voor het nemen van beslissingen binnen het bijbehorende domein. Verantwoordelijkheden in plaats van het hiërarchische niveau bepalen de positie van de rol in het besluitvormingsproces (Schell and Bischof 2021). In holacratische organisaties worden individuen verantwoor delijk gehouden voor de keuzes die ze maken bij het wer ken aan bepaalde resultaten vanuit hun rol(len) in plaats van voor de specifieke resultaten; deze kunnen namelijk worden beïnvloed door zaken waarop betreffende indivi duen geen invloed hebben (Robertson 2015b;Bernstein et al 2016).…”
Section: Radicale Decentralisatieunclassified